Attentional focus modulates physiological response to arousal in a competitive putting task - Rawls, Bobby; Finomore, Victor (Frontiers in Psychology, 2024)
Attentional focus during the execution of perceptual motor tasks has been shown to affect performance outcomes. The purpose of this study is to assess the physiological changes prompted by attentional focus in various levels of stress. Thirty-six healthy young males and females were randomized into groups and directed on attentional focus in a staged putting competition scenario intended to elicit competitive anxiety. External focus groups experienced less internal workload at all arousal levels and preserved heart rate variability measures when audiovisual distraction was introduced.